2019
DOI: 10.1093/qmath/haz017
|View full text |Cite
|
Sign up to set email alerts
|

Dolbeault cohomology of complex nilmanifolds foliated in toroidal groups

Abstract: It is conjectured that the Dolbeault cohomology of a complex nilmanifold X is computed by left-invariant forms. We prove this under the assumption that X is suitably foliated in toroidal groups and deduce that the conjecture holds in real dimension up to six.Our approach generalises previous methods, where the existence of a holomorphic fibration was a crucial ingredient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In many (and conjecturally all) cases [16], the inclusion A inv X ⊆ A X is an E 1 -isomorphism. In particular, this holds in complex dimensions up to 3 [18].…”
Section: Nilmanifoldsmentioning
confidence: 72%
“…In many (and conjecturally all) cases [16], the inclusion A inv X ⊆ A X is an E 1 -isomorphism. In particular, this holds in complex dimensions up to 3 [18].…”
Section: Nilmanifoldsmentioning
confidence: 72%
“…Sönke Rollenske is grateful to the other authors for the invitation to join the project at a relatively late stage. He is also grateful to A. Fino and J. Ruppenthal for many discussions about the Dolbeault cohomology of nilmanifolds that culminated in the paper [13]. We are also pleased to thank the anonymous referee for valuable remarks and suggestions for a better presentation of our results.…”
mentioning
confidence: 86%
“…In complex case, the J -compatible ascending series may not give a torus fibration resolution (see Example 3.6 in [23] or [13]). But our main theorem implies the following result.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the first example of a compact symplectic manifold that does not admit any Kähler metric happens to be a nilmanifold, the well known Kodaira-Thurston manifold, which is a primary Kodaira surface ( [58,90]). It is well known that the de Rham cohomology of nilmanifolds and completely solvable solvmanifolds can be computed in terms of invariant forms (according to Nomizu [70] and Hattori [52], respectively), and it is conjectured that the Dolbeault cohomology of nilmanifolds can also be computed using invariant forms (this conjecture has been proved for several particular cases, see [32,30,83,39]). In [18] it was shown that any nilmanifold with an invariant complex structure has holomorphically trivial canonical bundle, while it is known that this does not happen generally for solvmanifolds (see [38]).…”
Section: Introductionmentioning
confidence: 99%